Patterns of Waterpipe Tobacco Smoking Among U.S. Young Adults, 2013–2014 - Salloum, Ramzi G. (Am J Prev Med, 2016)
INTRODUCTION: Patterns of waterpipe smoking and associated other tobacco use were assessed among U.S. young adults (aged 18–24 years). METHODS: A descriptive analysis of baseline data (2013–2014) from the Population Assessment of Tobacco and Health Study was conducted in 2016. RESULTS: The study included 9,119 young adults—44% ever and 11% past–30 day waterpipe smokers (12% of men and 9% of women were past–30 day smokers). Among past–30 day smokers, waterpipe smoking frequency was distributed as follows: 4% daily, 23% weekly, 36% monthly, and 37% less than monthly. The average session exceeded 30 minutes for 79% of respondents. In this age group, 29% were exclusive waterpipe smokers, 16% were dual (waterpipe/cigarette) smokers, 8% were dual (waterpipe/e-cigarette) users, 19% were waterpipe/cigarette/e-cigarette users, and 28% presented with other combinations of poly use. CONCLUSIONS: Waterpipe smoking is widespread among U.S. young adults. Although waterpipe patterns are predominantly intermittent, the average smoking session provides prolonged exposure. Waterpipe smoking among young adults is primarily characterized by the use of flavored tobacco, the café culture, and poly tobacco use. Rising trends in waterpipe smoking among U.S. youth warrant a strong regulatory response to prevent future waterpipe-related morbidity and mortality.